The Role of PKK Saving Loan Against Community Economic Empowerment Malang City - Agustine, Siti Revina; Prajawati, Maretha Ika (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2023)
PKK savings and loans activities are an activity that flows from members' deposits or commonly called savings and money from member deposits will be turned into loans for members. The purpose of holding this savings and loans activity is to assist the community in flowing unused funds and assist the community in meeting the needs of the pressed or who are dependent on loan shark debt. In order to get deeper results, this study used the descriptive method of qualityf. Family Empowerment and Welfare or PKK rt 4 is located in rt 4 rw 12 Purwodadi village, Blimbing district, Malang City. The purpose of PKK rt 4 in the role of savings and loans is to reduce the community's dependence on loan sharks and provide business capital to small sector businesses that are still in the context of rt 4. The role of Savings and Loans in community economic empowerment, especially in reducing dependence on loan sharks, has been going well so some members have switched because the interest is lower than loan sharks and the interest itself will be distributed thoroughly to members in the form of Residual Business Results (SHU) at the end of the period.